How to Improve Reseller Performance? The Role of Maslahah Brand Resonance - Any Setyarini; Mohamad Sodikin; Nuswantoro (Universitas Darussalam Gontor, 2023)
Brand resonance is the highest level in Customer-Based Brand Equity (CBBE). Customer-Based Brand Equity is the differential effect of consumers on brand understanding that arises from experience with the brand. Meanwhile, brand resonance is the degree of relationship that consumers feel to a particular brand. Brand resonance is seen at the level of the psychological relationship between the customer and the brand, and the actions that result from loyalty. The study of brand resonance is still limited to profitable aspects and for its own sake, so there is no benefit for profit hereafter. This study proposes the concept of maslahah brand resonance as a new concept that has characteristics and dimensions of maslahah that are beneficial for business and profits in the hereafter, so that the orientation of the achievement is not only in the world but also in building a direct relationship with Allah SWT. This research is based on the view that consumers who are religious, hold fast to their religious beliefs will affect their consumption behavior. The theoretical contribution of this new concept is in the development of branding theory so that it has a wider scope. The managerial implication is that SME managers can apply brand resonance problems as an effort to build reseller performance improvements.